Effects of Early Resistance Training After Liver Transplantation Procedures: A Randomized Controlled Pilot Trial - Tuba Yüksel Ergene; Didem Karadibak; Ramazan Dönmez; Kâmil Yalçın Polat (Turkish Journal of Gastroenterology, 2022)
Background: Exercise interventions improve muscle performance and functionality when applied more than 6 months after liver trans- plantation, but no studies have reported on earlier exercise interventions. Hence, we assessed the effects of early resistance training on functional outcomes in adult liver recipients. Methods: The study included 30 liver transplantation patients (53.2 ± 12.4 years) randomly assigned to a training group (n = 15) or a control group (n = 15). Data collected preoperatively and 4 and 8 weeks post-surgery were analyzed, including peripheral and respiratory muscle strength, exercise capacity, physical performance, and fatigue. An 8-week physiotherapy program was applied (training group: standard physiotherapy + resistance training; control group: standard physiotherapy) for 2 sessions/day, 5 days/week. Results: Baseline data showed a homogeneous distribution in the between-group comparisons. In the within-group analysis; EG showed higher improvements in physical performance (TG: P = .001, CG: P = .05) and fatigue perception (TG: P = .001; CG: P = .006), than the CG. The TG showed eight-week improvements in exercise capacity, peripheral muscle strength, and maximal inspiratory pressure (P = .001), and maximal expiratory pressure (P = .047), while CG remained unchanged (P > .05). In the between-group analysis; the improvements indicated significant differences in deltoid strength and fatigue perception, in favor of the TG (P < .05). A change of 0.9 kg in peripheral muscle strength and >37.8 m in 6-min walk distance (6MWD) was determined, representing clinically significant improvement in liver recipients. Conclusion: Early resistance training may improve muscle strength, exercise capacity, physical performance, and fatigue perception in liver recipients, when added to standard physiotherapy. The estimated minimal clinically important differences are meaningful to clini- cians in setting liver transplanted patient-specific goals. Cite this article as: Yüksel Ergene T, Karadibak D, Dönmez R, Polat KY. Effects of early resistance training after liver transplantation procedures: A randomized controlled pilot trial. Turk J Gastroenterol. 2022;33(10):852-861.